New Adjunctive Therapy for Antibody-Mediated Rejection - Suttiruk, Pongpon; Tangweerapong, Kampantong; Homkrailas, Piyavadee (Journal of the Nephrology Society of Thailand, 2023)
Antibody-mediated rejection is one of the most serious complications after kidney transplantation. Rejection is the second most common cause of graft lost following death with functioning graft. The current standard treatment consists of combined plasmapheresis and intravenous immunoglobulin, which aims at removing alloantibody. The recent systematic review revealed variable responses among different studies ranging between 0 - 83%. With better understanding of the complex mechanisms underlying antibody-mediated rejection, other novel adjunctive therapy has been increasingly used in addition to the standard treatment. Current promising adjunctive therapies are rituximab which targets B-cells, bortezomib which targets plasma cells and eculizumab which targets the complement system. Alkylating agents and anti-thymocyte globulin have been proven ineffective. Other treatments that may add benefits to the standard treatment include imlifidase, interleukin-6 receptor antagonist, interleukin-6 antibody, and CD-38 monoclonal inhibitor.